Investigation on the self-recovery characteristics of PLC fabricated by melt-drawing method - Susan, See (2018)
Biodegradable polymer fiber has been widely used in the medical industry. There are several surgical applications where it can be applied such as tissue engineering, suturing, and hemostasis. Although it is still attracting much attention, such biomaterials are yet to be commonly chosen for medical uses due to a lack of information. Further research and investigation has to be carried out. There are various ways in which a polymer fiber can be fabricated – melt-spinning, dry-spinning and wet-spinning. Only the method of melt-spinning in polymer fiber fabrication, also known as melt-drawing method, will be discussed in this study. The melt-drawing machine has been built in a way for simple extraction of polymer and creation of fiber substrate. Fibers of different properties can be created by adjusting the controlled variables of the machine. Such variables include the lateral and rotational speed of the machine, length of the fiber and the orifice-mandrel height. The aim of this project is to fabricate polymer substrate of different properties and investigate their characteristics. Mechanical test such as puncture resistance test will be carried out to investigate the mechanical properties of each fiber sample. The individual fiber size can also be found out by using the Scanning Electron Microscope (SEM). The fibers will then be grouped into different categories based on the above tests – puncture resistance test and SEM. This research can help to provide information of biodegradable polymer fiber, which might be useful for future medical research or applications.